A Year of Trump: The Politics and Realities of President Trump’s Economic Policies - Kennedy, Brian (Thammasat Review of Economic and Social Policy, 2017)
The election of Donald Trump came as a surprise to the vast majority of political scientists, election forecasters, and senior political office holders, of both political parties. On top of that, then candidate Trump ran a decidedly unconventional political campaign. He spoke in broad outlines about what he was for, but gave very few specifics about what he would actually do. Few republicans sought to emulate Trump, and thus almost all other Republicans running for office ran on more traditional republican themes. President Trump thus has become the face of the Republican party, but he is only one man in the U.S. Governmental system. The most important one, yes, but one who still has limited powers to achieve any policy goals without working in concert with republican congressional majorities, or through the vast federal bureaucracy he now at least nominally heads. This paper seeks to detail out the relationships and constraints that are at play in the Donald Trump Presidency, to attempt to see what impact on economic policy, and through that policy what impact on the real economy, has occurred, and will continue as President Trump’s enters his second year in office.